Kontribusi Pajak Daerah Dan Retribusi Daerah Terhadap Peningkatan Pendapatan Asli Daerah Dalam Rangka Pelaksanaan Otonomi Daerah (Studi Di Tiga Daerah Di Propinsi Sumatera Barat) - Frenadin Adegustara; Syofiarti '; Titin Fatimah (Jurnal Ilmu Hukum, 2011)
Crash of regional autonomy has changed the paradigm of local governance. With these changes regions are given broad authority to regulate in the area of ​​governance including managing the financial resources of existing sources. Income is one of the major sources of regional funding within the framework of the implementation of decentralization. Regional taxes and levies have a very important role in supporting efforts to increase revenue (PAD). For collection of local taxes and levies are implemented by regulations issued local regulations. impacts that arise then are number of new regulations to appear the regulation of taxes and charges of disrupting public and entrepreneurs created the conditions are not conducive to economic development and national investment. In addition, regulations that lead to the occurrence of new levies, which in turn creates a high cost economy the national economic burden. The fact that there are many rules, regulations revoked by the Government accordance with the authority granted by the Act that the Government is authorized to evaluate each generated local regulations.